ON SPECIAL STRONG DIFFERENTIAL SUBORDINATIONS USING A NEW MULTIPLIER TRANSFORMATION AND RUSCHEWEYH DERIVATIVE - Swamy, SR (Journal of Global Research in Mathematical Archives(JGRMA), 2013)
Â Abstract: In this paper we have established several strong differential subordinations regarding the extended operator obtained as a linear combination of extended Ruscheweyh derivative and an extended new multiplier transformation. A certain subclass of analytic functions is introduced by means the new operator.